Biogenesis of Metal Nanoparticles - Samuel, Jesse Sebastian (My University, 2007)
Nanotechnology can best be considered as a description of activities at the level of atoms and molecules that have applications in the real world. A nanometer is a billionth of a meter, that is, about 1/80,000 of the diameter of a human hair, or 10 times the diameter of a hydrogen atom. The field of nanotechnology has generated great enthusiasm in recent years because of its expected impact on various fields of sciences. For the advancement of nanotechnology, development of reliable procedures for the synthesis of nanoparticles of controlled size and chemical composition is imperative. Many chemical routes are known to use toxic chemicals for the synthesis of the nanoparticles. The need-of-the-hour, however is to evolve procedures for nanoparticles synthesis through environmentally benign routes. Researchers in this field, therefore, have been eagerly looking at biological systems as alternative ecofriendly systems. The present work was carried out to examine the formation of gold nanoparticles by the fungi viz. Cladosporium resinae, Aspergillus niger and Paecilomyces variotii. The work culminated into the following results: XRD analysis confirming the presence of elemental gold in the biomass of test fungi. Light scattering (Nanosight™ technology) analysis confirming the formation of nano-sized particles extracellularly.
Keywords: Biogenesis; Actinomycetes; Nanomaterials; Magneto-Tacticbacteria; Murray